2023
DOI: 10.1021/jacs.3c08336
|View full text |Cite
|
Sign up to set email alerts
|

Showcasing Different G-Quadruplex Folds of a G-Rich Sequence: Between Rule-Based Prediction and Butterfly Effect

Yoanes Maria Vianney,
Nina Schröder,
Jagannath Jana
et al.

Abstract: In better understanding the interactions of Gquadruplexes in a cellular or noncellular environment, a reliable sequence-based prediction of their three-dimensional fold would be extremely useful, yet is often limited by their remarkable structural diversity. A G-rich sequence related to a promoter sequence of the PDGFR-β nuclease hypersensitivity element (NHE) comprises a G 3 -G 3 -G 2 -G 4 -G 3 pattern of five G-runs with two to four G residues. Although the predominant formation of three-layered canonical Gq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Such a pattern of glycosidic bond angles with both homopolar and heteropolar tetrad stacking has more frequently been observed for an antiparallel topology in a potassium ion solution. [21][22][23] Based on these findings, the G-quadruplex is suggested to adopt a chairtype topology with a counter-clockwise lateral loop progression termed-(lll) according to the notation introduced by Webba da Silva. [24] In analogy to the bromo-substituted 32Br TelQD employed in a recent study and shown to fold into a single topology (Table 1), [19] a most downfield-shifted resonance at 14.34 ppm showing a strong NOE contact to A30 H2 can unambiguously be identified through a residue-specific 15 N-labeling to be an imino proton of N1-protonated residue A30 positioned within the third lateral loop (Figure S3).…”
Section: Telqd Adopts An Antiparallel Chair-type Topology At Acidic Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a pattern of glycosidic bond angles with both homopolar and heteropolar tetrad stacking has more frequently been observed for an antiparallel topology in a potassium ion solution. [21][22][23] Based on these findings, the G-quadruplex is suggested to adopt a chairtype topology with a counter-clockwise lateral loop progression termed-(lll) according to the notation introduced by Webba da Silva. [24] In analogy to the bromo-substituted 32Br TelQD employed in a recent study and shown to fold into a single topology (Table 1), [19] a most downfield-shifted resonance at 14.34 ppm showing a strong NOE contact to A30 H2 can unambiguously be identified through a residue-specific 15 N-labeling to be an imino proton of N1-protonated residue A30 positioned within the third lateral loop (Figure S3).…”
Section: Telqd Adopts An Antiparallel Chair-type Topology At Acidic Phmentioning
confidence: 99%
“…Interestingly, formation of a (3 + 1) hybrid topology with a propeller, diagonal, and lateral loop has only rarely been observed. [21,28] Here, it may be a consequence of the hairpin sequence, forming a first propeller loop that prevents base pairing of its 5'-and 3'-terminal C and G residues now located at opposite faces of the G-core. [17] Rather than remaining unpaired, 3'-terminal G18 engages in a G-tetrad to release G21 in a register shift for participation in a sterically more relaxed 4nt diagonal loop.…”
Section: Telqd Adopts An Antiparallel Chair-type Topology At Acidic Phmentioning
confidence: 99%
“…The core of a G4 structure is composed of a stack of multiple G-tetrads stabilized by central cations, , such as K + or Na + . Studies over the last few decades have shed light on the polymorphism of G4s. ,, G4 structures are commonly classified based on the strand polarity: (i) parallel or (4 + 0), where all four strands are in one direction; (ii) antiparallel or (2 + 2), where two pairs of strands are in opposite directions; (iii) hybrid or (3 + 1), where three strands run in one direction and the fourth strand runs in the opposite direction. A good example of G4 diversity is presented by the human telomeric sequences (TTAGGG) n .…”
mentioning
confidence: 99%